2019
DOI: 10.1016/j.brs.2018.12.227
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transcranial direct current stimulation on exercise performance: A systematic review and meta-analysis

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
142
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(147 citation statements)
references
References 95 publications
1
142
2
2
Order By: Relevance
“…Neuromodulation to augment performance in sports is no science fiction. Several opinion papers and systematic review and meta-analysis articles discussed the feasibility of tDCS as a performance enhancer in athletes (Bolognini et al, 2009;Banissy and Muggleton, 2013;Davis, 2013;Reardon, 2016;Edwards et al, 2017;Angius et al, 2018b;Machado et al, 2019). Interestingly, tDCS is capable of increasing isometric strength (Hazime et al, 2017;Vargas et al, 2018), countermovement jump performance (Lattari et al, 2020) and endurance performance (Okano et al, 2015) even in trained athletes.…”
Section: Performance Enhancement Using Non-invasive Brain Stimulationmentioning
confidence: 99%
“…Neuromodulation to augment performance in sports is no science fiction. Several opinion papers and systematic review and meta-analysis articles discussed the feasibility of tDCS as a performance enhancer in athletes (Bolognini et al, 2009;Banissy and Muggleton, 2013;Davis, 2013;Reardon, 2016;Edwards et al, 2017;Angius et al, 2018b;Machado et al, 2019). Interestingly, tDCS is capable of increasing isometric strength (Hazime et al, 2017;Vargas et al, 2018), countermovement jump performance (Lattari et al, 2020) and endurance performance (Okano et al, 2015) even in trained athletes.…”
Section: Performance Enhancement Using Non-invasive Brain Stimulationmentioning
confidence: 99%
“…Transcranial direct current stimulation (tDCS) is a safe method for modulating the excitability of brain regions noninvasively by inducing a low-amplitude current flow between two or more electrodes placed on the scalp [9]. Several systematic reviews and meta-analyses have demonstrated that anodal tDCS applied over M1 can improve balance control, promote muscle strength and muscular endurance, and enhance exercise performance in cycling [10][11][12]. Studies have also shown that anodal tDCS designed to target the sensorimotor regions of the brain improves physical performance, including muscle strength and sensory function [13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, tDCS could also improve exercise performance and reduce neuromuscular fatigue. A recent meta-analysis by Machado et al assessed the tDCS effects on performance improvement during different exercises (muscle strength exercise or whole body dynamic cyclic exercise) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, anodal tDCS would not have any effect on the isometric strength of the upper or lower limbs and few studies have evaluated the effects of tDCS on isokinetic or dynamic muscle strength [3]. To sum up, many studies have demonstrated a positive enhancement of performance using tDCS [4][5][6] while others failed to find any improvement [7][8][9]; therefore, no particular consensus could be made based on the literature.…”
Section: Introductionmentioning
confidence: 99%